2006
DOI: 10.1007/s00442-005-0303-1
|View full text |Cite
|
Sign up to set email alerts
|

Predator defense along a permanence gradient: roles of case structure, behavior, and developmental phenology in caddisflies

Abstract: Species replacements along freshwater permanence gradients are well documented, but underlying mechanisms are poorly understood for most taxa. In subalpine wetlands in Colorado, the relative abundance of caddisfly larvae shifts from temporary to permanent basins. Predators on caddisflies also shift along this gradient; salamanders (Ambystoma tigrinum nebulosum) in permanent ponds are replaced by predaceous diving beetles (Dytiscus dauricus) in temporary habitats. We conducted laboratory and field experiments t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 58 publications
1
42
0
Order By: Relevance
“…We hypothesized that those case materials that have been experimentally documented to resist greater forces (i.e., mineral cases) would provide greater resistance against predation and increase chances of survival, as has been demonstrated previously (Otto and Svensson 1980; Johansson 1991; Nislow and Molles 1993; Wissinger et al 2006). Although the relative strength of the cases used in this study was not measured, these cases qualitatively appeared to reflect this gradient; rock cases were generally stronger than stick cases, which were stronger than leaf cases (BGG personal observation).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…We hypothesized that those case materials that have been experimentally documented to resist greater forces (i.e., mineral cases) would provide greater resistance against predation and increase chances of survival, as has been demonstrated previously (Otto and Svensson 1980; Johansson 1991; Nislow and Molles 1993; Wissinger et al 2006). Although the relative strength of the cases used in this study was not measured, these cases qualitatively appeared to reflect this gradient; rock cases were generally stronger than stick cases, which were stronger than leaf cases (BGG personal observation).…”
Section: Methodsmentioning
confidence: 97%
“…For example, Wissinger et al (2004) demonstrated that individual caddisflies that possessed a case were less likely to succumb to cannibalism compared to their caseless counterparts. Furthermore, although several species of caddisflies that build cases of different material had different survivorship against predatory salamanders, each had higher survival when left in their case relative to individuals of that species that were removed (Wissinger et al 2006). These results, in conjunction with the results presented here, indicate that case construction is an important adaptation for reducing predation.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, organisms inhabiting physically stressful environments often face life‐history constraints that force individuals to trade‐off resistance to biotic interactions with rapid development or efficient resource use (Power, Parker & Wootton ; Wissinger et al . ; Edwards & Stachowicz ). These trade‐offs may strengthen top‐down control in disturbed habitats.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence of trade‐offs between traits that facilitate coexistence with predators and those that facilitate the completion of larval development before ponds dry, the particular combinations of species vary among pond permanence types (temporary vs. permanent; Wissinger et al. , ). These closely related caddisfly larvae (Ruiter et al.…”
Section: Introductionmentioning
confidence: 99%